2017
DOI: 10.5796/electrochemistry.85.534
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure Engineering of Size-Quantized Semiconductor Particles for Photoelectrochemical Applications

Abstract: Semiconductor nanoparticles of several nanometers in size that exhibit the quantum size effect have recently been called "quantum dots". Their unique physicochemical properties, which are different from those of bulk material or molecules, have attracted much attention for various applications, because of the controllability and designability of electronic, optical, and photochemical properties by changing the size, shape, and chemical composition of particles. Many efforts have contributed to the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Multinary I–III–VI semiconductors and related materials exhibit unique composition-dependent physicochemical properties due to their structural tolerance to large nonstoichiometry, and they have attracted much attention for possible applications in various photofunctional devices such as solar cells , and photocatalyts. In addition to the tunability of their properties through chemical composition, controlling the size of these materials in a size-quantized regime is another strategy for obtaining the desired optical properties. Since nanoparticles of CuInS 2 , AgInS 2 , and their solid solution with ZnS , were reported to exhibit strong photoluminescence (PL) in the visible-light wavelength region, I–III–VI-based nanoparticles with well-controlled size, structure, and chemical composition have been intensively developed as novel quantum dots for practical use. Advantages of these materials include a direct band gap, nontoxic composition, and strong absorption coefficients in the visible to near-IR wavelength regions. For example, solid-solution nanoparticles of AgInS 2 –ZnS, AgInSe 2 –ZnSe, , AgGaS 2 –ZnS, and CuInS 2 –ZnS have tunable energy gaps ( E g s) depending on the particle size and Zn content in the particles and they exhibit a broad PL peak assignable to defect-site emissions, the peak wavelength of which decreases with an increase in the E g .…”
Section: Introductionmentioning
confidence: 99%
“…Multinary I–III–VI semiconductors and related materials exhibit unique composition-dependent physicochemical properties due to their structural tolerance to large nonstoichiometry, and they have attracted much attention for possible applications in various photofunctional devices such as solar cells , and photocatalyts. In addition to the tunability of their properties through chemical composition, controlling the size of these materials in a size-quantized regime is another strategy for obtaining the desired optical properties. Since nanoparticles of CuInS 2 , AgInS 2 , and their solid solution with ZnS , were reported to exhibit strong photoluminescence (PL) in the visible-light wavelength region, I–III–VI-based nanoparticles with well-controlled size, structure, and chemical composition have been intensively developed as novel quantum dots for practical use. Advantages of these materials include a direct band gap, nontoxic composition, and strong absorption coefficients in the visible to near-IR wavelength regions. For example, solid-solution nanoparticles of AgInS 2 –ZnS, AgInSe 2 –ZnSe, , AgGaS 2 –ZnS, and CuInS 2 –ZnS have tunable energy gaps ( E g s) depending on the particle size and Zn content in the particles and they exhibit a broad PL peak assignable to defect-site emissions, the peak wavelength of which decreases with an increase in the E g .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, much interest has been shown in nanocrystals of I–III–VI-based metal chalcogenide semiconductors, such as CuInS 2 , AgInS 2 , and their solid solutions with ZnS, as alternatives to conventional binary nanoparticles, such as CdSe, CdTe, and PbS, because they are composed of elements with less toxicity and exhibit physicochemical properties that can be controlled by their chemical composition as well as by their size. ,,, Because the absorption properties of multinary metal chalcogenide nanocrystals vary in a wide wavelength range from visible light to near-infrared light, these nanocrystals are useful materials as components to fabricate nanoscale heterojunctions. An appropriate combination of I–III–VI 2 nanocrystals and binary semiconductor nanocrystals can produce a type-II heterojunction, accomplishing spatial and efficient charge separation of photogenerated electrons and holes. For example, Teranishi and co-workers reported that holes photogenerated in the CuInS 2 /CdS heterotetrapod nanocrystals were localized in CuInS 2 core but that photoexcited electrons were delocalized in the whole particle .…”
Section: Introductionmentioning
confidence: 99%
“…This tendency was regarded as a quantum-size effect and has already been observed for semiconductor particles. 53–55…”
Section: Resultsmentioning
confidence: 99%
“…This tendency was regarded as a quantum-size effect and has already been observed for semiconductor particles. [53][54][55] Ideas for enhancing the STH conversion efficiency of a Z-scheme system As revealed by the electronic structure of photocatalytic Z-scheme systems in Fig. 1, there are five ideas for methods to enhance STH conversion efficiency for OWS by the systems.…”
Section: Electronic Structures Of Hec and Oec Nanoparticlesmentioning
confidence: 99%